The carrying capacity of a tourist destination. The case of a coastal Italian city - Elena Maggi; Franco Lorenzo Fredella (European Regional Science Association (ERSA), 2010)
In the last decades the world tourist flows rapidly grew and travel and tourism has become one of the world's highest priority industries and employers. According to UNWTO world tourism barometer, in 2008 international tourist arrivals reached 919 million (880 million in 2009, a cause of the international recession), with a growth of 72% since 1995. Italy, which accounts in 2009 43 millions of tourist arrivals, is one of the most preferred destinations. Tourism gives an important contribution to the regional and local economic development, but it causes also negative impacts mainly on the environment and social context. In particular, the uncontrolled development of the tourist activities and the intensive land exploitation can cause a rapid reduction of the environmental, cultural and social resources, with negative effects also on the tourism development and on the economic activity of the area. As a consequence, the relevance of this phenomenon and the simultaneous spreading of the sustainable development concept have pushed towards the identification of a more sustainable process of planning, development and management of the tourist activities. Thus, the tourism carrying capacity (TCC) approach has been developed and has become a real challenge for both planners and managers. The TCC assessment differs according to the different type of destinations: coastal areas, islands, protected areas, rural areas, mountain resorts and historical settlements. The present paper focuses on a coastal destination, which is normally associated with mass tourism, large scale construction and infrastructure, intensive land development and extensive urbanisation. The application of a carrying capacity to this type of destination makes the need to consider tourist density, the use of beaches and tourist infrastructure, congestion of facilities and transport infrastructure, sea pollution, waste production, etc. After a review of the TCC theory, the paper presents the application of the TCC assessment to a South Italy coastal destination, aiming at identifying the opportunities and the limits of the tourism development in such a destination and at developing some policy recommendations.
Keywords: 330